Regency Analysis of the Problem of Low Literacy Skills of Elementary School Students in Dompu - Khairul Khalqi; Sri Haryanti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the problems and low literacy skills of students, especially at the elementary school of Madrasah Ibtidaiyah (MI) Al-Faat Bara. This study uses a descriptive analysis method based on qualitative data through observations and interviews conducted at the elementary school of MI Al-Faat Bara. While the research subjects are elementary school students / MI. As well as the parents of the students. Based on the results of the study, it shows that the factors causing the low literacy skills of MI Al-Faat Bara students are: 1. Low interest in reading; 2. Insufficient facilities and infrastructure; 3. Relationships in the family; 4. The influence of cellphones and television; 5. Teachers have not maximized the model in learning to read.